TYPES OF COLLECTIONS - Nematov Mirsulton Alisher ugli (Web of Journals Publishing, 2025)
Operations on sets is one of the main concepts of set theory in mathematics. Operations on sets are mathematically important because they are widely used in the study of various mathematical theories and concepts, as well as in solving practical problems. This article provides detailed information about the basic operations performed on collections, their properties, and how to use them.
Keywords: Sets, mathematics, numbers, mathematics, statistics, probability theory, modeling, mathematical literacy.